Romiplostim in adults with newly diagnosed or persistent immune thrombocytopenia. Issue 12 (1st December 2020) - Lozano, Maria L.; Godeau, Bertrand; Grainger, John; Matzdorff, Axel; Rodeghiero, Francesco; Hippenmeyer, Jane; Kuter, David J.
ABSTRACT: Introduction : Three distinct phases are recognized in immune thrombocytopenia (ITP): newly diagnosed (≤3 months after diagnosis), persistent (>3–12 months after diagnosis), and chronic (>12 months). Several international guidelines/expert recommendations have been released in the past 2 years regarding the treatment of newly diagnosed/persistent ITP. Areas covered : Across the guidelines/expert recommendations, thrombopoietin receptor agonists (TPO-RAs), including romiplostim (the focus of this review), are recommended in newly diagnosed or persistent ITP for patients who fail to respond to corticosteroids or intravenous immunoglobulin (or where these are contraindicated). To identify data relating to romiplostim in adults with newly diagnosed or persistent ITP, we conducted a search of PubMed (with no time limit applied) and abstracts from 2019 EHA/ASH meetings using the term 'romiplostim.' Expert opinion : The findings from nine clinical trials, six real-world studies and ten case reports provide insight into the early use of romiplostim, which could help to reduce exposure to the adverse effects associated with prolonged corticosteroid use, as well as reduce the risk of severe bleeding. Additionally, given the durable responses observed in patients with newly diagnosed/persistent ITP, as well as the potential for treatment-free responses following discontinuation, romiplostim might help to avoid the need for subsequent treatment.